Abordajes restaurativos frente al ocio desviado eco-lesivo: ÁBACO : una propuesta de intervención restaurativa anti-basuraleza = Restorative approaches towards eco-harming deviant leisure : ÁBACO : a restorative justice intervention proposal against littering - Herrera Moreno, Myriam (Revista de victimología, 2023)
After several considerations on what is known as eco-victimology, in relation to the studies of green victimology, within the Spanish and, specifically, Andalusian context, a proposal for restorative intervention around what is known as basuraleza (littering) in relation to deviant leisure is made.